2018
DOI: 10.1002/ps.4788
|View full text |Cite
|
Sign up to set email alerts
|

High carbon dioxide concentration and elevated temperature impact the growth of weeds but do not change the efficacy of glyphosate

Abstract: The positive effect of high CO concentration on the growth of weeds does not impact the activity of glyphosate. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
4
11
0
1
Order By: Relevance
“…However, there was no significant effect on the efficacy of the herbicides, halosulfuron and glyphosate or their tank mix at the elevated CO 2 condition . Similar results were reported for glyphosate efficacy against four different weed species by Jabran and Doğan. There has been little explanation in literature to describe no effect of elevated CO 2 concentration on the herbicide efficacy despite of a positive effect on weeds' biology.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, there was no significant effect on the efficacy of the herbicides, halosulfuron and glyphosate or their tank mix at the elevated CO 2 condition . Similar results were reported for glyphosate efficacy against four different weed species by Jabran and Doğan. There has been little explanation in literature to describe no effect of elevated CO 2 concentration on the herbicide efficacy despite of a positive effect on weeds' biology.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies evaluating the efficacy of herbicides (mainly glyphosate) against different weeds at elevated CO 2 have reported mixed results. Some studies have reported no significant effect of elevated CO 2 on glyphosate efficacy against different weeds . For instance, Marble et al reported significant growth improvement in Cyperus rotundus L. and Cyperus esculentus L. at an elevated CO 2 concentration (600 ppm) when compared to the ambient CO 2 concentration (400 ppm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present research suggests that S. cannabina grown in an elevated [CO 2 ] of 700 ppm will be taller, with more leaves, a high growth index, longer root length, greater fresh and dry biomass, and greater chlorophyll content when compared to plants grown in an ambient [CO 2 ] of 400 ppm (Figures 1-4). These findings acquiesce with others in predicting that an elevated [CO 2 ] of 700 ppm will have a significant positive effect on the growth and biomass production of S. cannabina [13,26]. In a previous study, Xanthium strumarium L., a C3 weed, when grown in an elevated [CO 2 ] environment presented a higher leaf area, leaf photosynthesis, and dry biomass [27].…”
Section: Effect Of Different [Co 2 ]supporting
confidence: 84%
“…Previous studies have also demonstrated that global warming can affect the growth, phenology, and geographical distribution of weeds . Our study found that there was no difference in weed density between warming and control plots, though the number of weeds in year two was significantly higher than in year one.…”
Section: Discussionsupporting
confidence: 49%